Um estudo sobre os modos de apropriação do cinema por educadoras na escolarização de jovens e adultos - Faheina, Evelyn Fernandes Azevedo (2012)
This study discusses the usage of movies in young and adult education. It assumes the conception of movies as an object of knowledge, which actively participates in the production, organization and dissemination of knowledge and expertise. This is based on the concept that, in the school routine, the appropriation of films by the educators should not serve the purposes of illustration of the content studied and entertainment only. On the contrary, one should recover the pedagogical sense of the film and understand it as mediator of knowledge. Given this approach, the study seeks to know, more precisely, how the educators who teach the cycles I and II of EJA, crowded schools in the Polo I of João Pessoa PB municipal schools, have appropriated of the movies at school. This is a qualitative study which makes usage especially of areas of Education and Film to clarify some issues, among which, those related to the film as a mediator of knowledge and its mode of appropriation by educators as an object of knowledge. The data collection techniques adopted to this research were systematic observation and the semi-structured interview, and to analyze the statements of the interviewees, it was used the technique of content analysis, directed by Laurence Bardin (2011). The study concludes that teachers of young and adult education have appropriated of the movies as an illustration of the school curriculum and subjects studied in the classroom, and its usage as additional resource and secondary in teaching activities is one of the consequences that emerge from this process.